Homeostatic and pathogenic roles of GM3 ganglioside molecular species in TLR4 signaling in obesity. (7th May 2020) - Kanoh, Hirotaka; Nitta, Takahiro; Go, Shinji; Inamori, Kei‐ichiro; Veillon, Lucas; Nihei, Wataru; Fujii, Mayu; Kabayama, Kazuya; Shimoyama, Atsushi; Fukase, Koichi; Ohto, Umeharu; Shimizu, Toshiyuki; et al.
Abstract: Innate immune signaling via TLR4 plays critical roles in pathogenesis of metabolic disorders, but the contribution of different lipid species to metabolic disorders and inflammatory diseases is less clear. GM3 ganglioside in human serum is composed of a variety of fatty acids, including long‐chain (LCFA) and very‐long‐chain (VLCFA). Analysis of circulating levels of human serum GM3 species from patients at different stages of insulin resistance and chronic inflammation reveals that levels of VLCFA‐GM3 increase significantly in metabolic disorders, while LCFA‐GM3 serum levels decrease. Specific GM3 species also correlates with disease symptoms. VLCFA‐GM3 levels increase in the adipose tissue of obese mice, and this is blocked in TLR4‐mutant mice. In cultured monocytes, GM3 by itself has no effect on TLR4 activation; however, VLCFA‐GM3 synergistically and selectively enhances TLR4 activation by LPS/HMGB1, while LCFA‐GM3 and unsaturated VLCFA‐GM3 suppresses TLR4 activation. GM3 interacts with the extracellular region of TLR4/MD2 complex to modulate dimerization/oligomerization. Ligand‐molecular docking analysis supports that VLCFA‐GM3 and LCFA‐GM3 act as agonist and antagonist of TLR4 activity, respectively, by differentially binding to the hydrophobic pocket of MD2. Our findings suggest that VLCFA‐GM3 is a risk factor for TLR4‐mediated disease progression. Synopsis: Analysis of GM3 ganglioside composition in human serum under chronic inflammation conditions reveals that the fatty acid chain length of GM3 ganglioside impacts the inflammatory activation of macrophages via direct modulation of TLR4 signaling. GM3 ganglioside in human serum is composed of a variety of fatty acids including long‐chain (LCFA) and very long‐chain (VLCFA). Serum VLCFA‐GM3 levels increase and LCFA‐GM3 levels decrease in metabolic disorders. GM3 by itself has no effects on TLR4 activation; however, VLCFA‐GM3 synergistically and selectively enhanced TLR4 activation by LPS/HMGB1while LCFA‐ and unsaturated VLCFA‐GM3 suppress TLR4 activation. GM3 interacts with extracellular regions of TLR4/MD2 complex, and modulates dimerization/oligomerization. Ligand‐macromolecular docking study suggested that VLCFA‐ and LCFA‐GM3 act as agonist and antagonist against TLR4 activation, respectively, by differentially binding to hydrophobic pocket of MD2. VLCFA‐GM3 could be a risk factor for TLR4‐mediated disease progression. Abstract : Analysis of GM3 ganglioside composition in human serum under chronic inflammation conditions reveals that the fatty acid chain length of GM3 ganglioside impacts the inflammatory activation of macrophages via direct modulation of TLR4 signaling.